Bacterial adhesion and biofilm formation on yttria‐stabilized, tetragonal zirconia and titanium oral implant materials with low surface roughness ‐ anin situstudy. Issue 7 (July 2016) - Al‐Ahmad, Ali; Karygianni, Lamprini; Schulze Wartenhorst, Max; Bächle, Maria; Hellwig, Elmar; Follo, Marie; Vach, Kirstin; Han, Jung‐Suk
Abstract : N/A: Bacterially‐driven mucosal inflammation and the development of periimplantitis can lead to oral implant failure. In this study, initial bacterial adhesion after 2 h, and biofilm formation after 1 day and 3 days, were analysed in situ on novel 3 mol % yttria‐stabilized tetragonal zirconia polycrystal samples, as well as on alumina and niobium co‐doped yttria‐stabilized tetragonal zirconia samples. Pure titanium implant material and bovine enamel slabs served as controls. The initially adherent oral bacteria were determined by 4', 6‐diamidino‐2‐phenylindole‐staining. Biofilm thickness, surface covering grade and content of oral streptococci within the biofilm were measured by fluorescence in situ hybridization. No significant differences between the ceramic and titanium surfaces were detectable for either initial bacterial adhesion or the oral streptococci content of the in situ biofilm. The oral biofilm thickness on the implant surfaces were almost doubled after three days compared to the first day of oral exposure. Nevertheless, the biofilm thickness values among the different implant surfaces and controls did not differ significantly for any time point of measurement after 1 day or 3 days of biofilm formation. Significant differences in the covering grade were only detected between day 1 and day 3 for each tested implant material group. The content of oral streptococci increased significantly in parallel with the increase in biofilm age from day 1 to day 3. In conclusion, oral implant zirconia surfaces with low surface roughness are comparable to titanium surfaces with respect to initial bacterial adhesion and biofilm formation.